Decision making of inmates: testing social information processing concepts using vignettes - Bowen, Kendra N. (Applied psychology in criminal justice, 2016)
Empirical research has established social information processing (SIP) theory as aprominent theory of youth aggression. However, little research on the theory exists in thecriminological research. The purpose of this study is to conduct a partial test of SIP theoryon a sample of 330 adult offenders using vignettes. Specifically, utilizing hierarchicalgeneralized linear modeling (HGLM), we examine self-reported situational decisionmaking (anger, intentions, goals, and response generation) and person-level variables(anger and hostile attribution bias) in predicting reported outcomes to high risk for violence vignettes. Results indicate that SIP and anger variables are important to further examinewith the adult criminal population.